Prevalence, clinical profile, maternal and perinatal outcomes of pregnancies complicated with obstructed labor at a teaching hospital in Tigray, Ethiopia: A five-year retrospective cross-sectional study - Hale Teka; Mussie Alemayehu; Awol Yemane; Marta Abrha; Tsega Gebremariam; Ephrem Berhe; Bisrat Tesfay Abera; Ashenafi Tekle; Habtom Tadesse; Hiluf Ebuy Abraha; Yibrah Berhe (PLoS ONE, 2025)
Background Obstructed labor remains a significant direct obstetric complication that leads to increased maternal and neonatal morbidity and mortality, particularly in resource-poor settings. Understanding the prevalence, clinical profile and maternal and perinatal outcomes is critical to developing targeted interventions to improve maternal and neonatal survival. Methods An institutional based retrospective cross-sectional study was conducted at Ayder Comprehensive Specialized Hospital (ACSH) in Tigray, Ethiopia, between 2017 and 2021. Sociodemographic, obstetric and clinical data as well as maternal and neonatal outcomes were extracted and analysed using descriptive statistics. Results The prevalence of obstructed labor during the study period was 0.38% [95% CI: 0.36% to 0.42%]. The mean age of the mothers was 30 years (SD = 6.04), half were between 25 and 34 years old. Most mothers (89%) were from the Tigray region, while the remaining were from neighbouring districts of Afar and Amhara regional states. More than two-thirds of these mothers lived in rural areas. Eighty-two percent attended at least one antenatal care visit, and 87% were referred. The average duration of labor was 14.5 hours [IQR = 8.24]. On admission, 28% were hypotensive, 65% were tachypneic, and nearly 68% had no fetal cardiac activity. Maternal complications included uterine rupture (65%), anemia (78%), postpartum hemorrhage (71%), and sepsis (23%). There were two maternal deaths. Cephalopelvic disproportion was present in 73% of cases. There were dismal neonatal outcomes with 70% mortality. Conclusions Obstructed labor continues to be a life-threatening obstetric emergency in this region, resulting in severe maternal complications, maternal deaths and extremely high neonatal mortality rates. Strengthening referral systems, improving capacity for emergency obstetric care, raising public awareness and early interventions are essential to reduce these avoidable burdens and achieve maternal and neonatal health goals.